Problematic Aspects of Technology Education in Slovakia - Haskova, Alena; Mandulakova, Silvia; Van Merode, Dirk (Communications - Scientific letters of the University of Zilina, 2017)
In current technology-based societies, understanding fundamental scientific concepts and theories and the ability to structure and solve scientific problems are more important than ever before. Understanding of science and technology is central to young people’s readiness for their life in the current society. Moreover, each society, not only the technology-based one, needs creative technicians and engineers. That is why technology education has long been an integral part of (school) education although various societies and countries carry out this type of education in different ways. The paper presents the results of various researches and studies aimed at the current development and quality of technology education done mainly at lower secondary schools in Slovakia where technology education was taught within the school subject of the same name – technology education before the school reform (2008), while currently it is taught as part of the school subject called technology. The paper focuses its attention on analyses and discussions of the most problematic aspects of this development.